2004
DOI: 10.1111/j.1365-4632.2004.02403.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of autologous transplantation of noncultured epidermal suspension in two different dilutions in the treatment of vitiligo

Abstract: We contend that the minimum number of melanocytes required to produce satisfactory repigmentation is probably in the range of 210-250/mm(2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
44
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 15 publications
10
44
3
Order By: Relevance
“…When assessing the clinical and treatment characteristics associated with optimal pigmentation, we found that a statistically significant higher melanocytes were transplanted in patients achieving RP > 75% (Table 1). In our study the mean number of melanocytes transplanted that was associated with optimum pigmentation was 1187 cells/cm 2 , which is much less than that described by Tegta et al 14 This lesser requirement of melanocyte for optimal pigmentation than epidermal cell suspension may be due to the different morphology and ultrastructural characteristics of hair follicle melanocytes, being larger, more dendritic and a higher synthetic capacity. 8 Hair follicle is an important reservoir of melanocytes and their precursor cells.…”
Section: 13contrasting
confidence: 77%
See 1 more Smart Citation
“…When assessing the clinical and treatment characteristics associated with optimal pigmentation, we found that a statistically significant higher melanocytes were transplanted in patients achieving RP > 75% (Table 1). In our study the mean number of melanocytes transplanted that was associated with optimum pigmentation was 1187 cells/cm 2 , which is much less than that described by Tegta et al 14 This lesser requirement of melanocyte for optimal pigmentation than epidermal cell suspension may be due to the different morphology and ultrastructural characteristics of hair follicle melanocytes, being larger, more dendritic and a higher synthetic capacity. 8 Hair follicle is an important reservoir of melanocytes and their precursor cells.…”
Section: 13contrasting
confidence: 77%
“…Based on the studies conducted in epidermal cell suspension, the authors had speculated the cell requirement to be less than 2000 cells/cm 2 . 4,14 In the present study, we found a significant correlation between the number of melanocytes transplanted and repigmentation rate at 24 week. When assessing the clinical and treatment characteristics associated with optimal pigmentation, we found that a statistically significant higher melanocytes were transplanted in patients achieving RP > 75% (Table 1).…”
Section: 13mentioning
confidence: 64%
“…In the present study, in the majority of the responding lesions (85.0%), a diffuse repigmentation pattern was observed, but there were rather than a typically follicular pattern in 10.0% or repigmentation from the perilesional margins in only 5.0% this is the same observed by Mulkar study, [15] Sobhy [12] and this observation may be due to spreading of melanocytes rich suspension liquid to all of treated areas giving chance to diffuse spread of transplanted melanocytes and so diffuse repigmentation pattern. In the present study the transplanted melanocytic cell count per mm 2 ranged between 210-300 cells per mm 2 donner skin graft which were enough to induce repigmentation and this was similar in accordance to GR Tegta et al study [17] that found that the optimal melanocytes count was 210-250 cells per mm 2 donner skin graft and so no great difference in range of these transplanted cells statistically to affect significantly degree of repigmentation. This study revealed that the time of initial repigmentation for the actively treated areas ranged between one week and three weeks, this was the same in comparison to what is done by Sobhy [12] and Flabella [13].…”
Section: Discussionsupporting
confidence: 76%
“…13 Lesions on the hands and feet (ie, acral vitiligo) have typically been the most difficult to treat with medical modalities. 8,14 Anbar et al 15 reported repigmentation of between 0% and 25% after treating 39 patients with acral lesions with 6 months of narrowband ultraviolet B. Considering 22% of patients achieved excellent results (and 22% receiving good repigmentation and 22% receiving fair pigmentation), there may be a particular role for the MKTP in management of vitiligo involving certain parts of the hands and feet where the tips of the fingers and toes are not involved.…”
Section: Discussionmentioning
confidence: 96%